2021
DOI: 10.3389/fnins.2021.631087
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Brain Magnetic Resonance Imaging Findings and the Cognitive and Motor Performance in the Elderly: The Shanghai Changfeng Study

Abstract: BackgroundThe frequently discovered incidental findings (IFs) from imaging observations are increasing. The IFs show the potential clues of structural abnormalities underlying cognitive decline in elders. Detecting brain IFs and their relationship with cognitive and behavioral functions helps provide the information for clinical strategies.MethodsFive hundred and seventy-nine participants were recruited in the Shanghai Changfeng Study. All participants performed the demographic, biochemical, and cognitive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…White matter hyperintensities exist on a spectrum from a clinically insignificant finding to pathologic white matter disease [ 24 ], but reporting thresholds are poorly standardised. This issue is exemplified in the findings of Wang et al [ 76 ], who reported the prevalence of hyperintensities stratified into grades in 579 patients. At the lowest threshold, white matter intensities were observed in 566/579 patients (97.8%) [ 76 ].…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…White matter hyperintensities exist on a spectrum from a clinically insignificant finding to pathologic white matter disease [ 24 ], but reporting thresholds are poorly standardised. This issue is exemplified in the findings of Wang et al [ 76 ], who reported the prevalence of hyperintensities stratified into grades in 579 patients. At the lowest threshold, white matter intensities were observed in 566/579 patients (97.8%) [ 76 ].…”
Section: Methodsmentioning
confidence: 93%
“…This issue is exemplified in the findings of Wang et al [ 76 ], who reported the prevalence of hyperintensities stratified into grades in 579 patients. At the lowest threshold, white matter intensities were observed in 566/579 patients (97.8%) [ 76 ]. Thus, we did not pool these findings.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…1,2 With the wider use of brain MRI in clinical practice, the cases of incidental imaging ndings in patients with cognitive impairment have been increasing. 3,4 Studies have demonstrated that majority of these incidental ndings do not indicate the requirement of any treatment, although positive ndings have been more frequently observed in patients with cognitive impairment compared to healthy elderly. 3 However, incidental vascular ndings such as aneurysm or stenosis are not well documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Brain magnetic resonance imaging (MRI) plays a crucial role in the diagnostic work-up and follow-up of patients with cognitive impairment ( 1 , 2 ). With the wider use of brain MRI in clinical practice, the cases of incidental imaging findings in patients with cognitive impairment have been increasing ( 3 , 4 ). Studies have indicated that positive findings have been more frequently observed in patients with a cognitive impairment compared to healthy elderly, although majority of these incidental findings do not indicate the requirement of any treatment ( 3 ).…”
Section: Introductionmentioning
confidence: 99%